The role of green rust in the environment: a review O papel do green rust no ambiente - Lucia H. G. Chaves (Revista Brasileira de Engenharia Agrícola e Ambiental)
Iron(II)-iron(III) hydroxy-salts known as green rusts (GRs) initially were identified and studied as corrosion products of steel and iron. Recently they were discovered as minerals present in hydromorphic soils and sediments. Different studies have suggested that GRs, due to their high reactivity, play an important role in the fate and transport of many contaminants in suboxic soils, sediments and aquifers where microbial reduction rates are limited by low carbon content. Also, GRs have considerable potential for applications such as water-purification processes and gas adsorbents. However, as GRs are only a transient state during the reduction of ferric iron and are converted to more stable forms, it is still necessary to continue studies about their behavior. Hidróxidos de ferro (II)-ferro(III) conhecidos como "green rust" (GR), inicialmente foram identificados e estudados como sendo os produtos provenientes da corrosão do aço e do ferro. Recentemente esses hidróxidos foram encontrados na forma mineral em solos hidromórficos e em sedimentos. Devido a sua alta reatividade, muitos trabalhos têm mostrado que esses hidróxidos desempenham um importante papel no destino e transporte de muitos contaminantes em solos subóxicos, sedimentos e aqüíferos, onde a taxa de redução microbiana é limitada pelo baixo conteúdo de carbono. Os "green rusts" também podem ser utilizados nos processos de purificação de águas e como adsorventes de gases. Entretanto, como GR são considerados uma fase transitória durante a redução do íon férrico e são, rapidamente, convertidos para formas mais estáveis, é necessário que os estudos sobre seu comportamento continuem.